2019
DOI: 10.1007/s10584-019-02417-6
|View full text |Cite
|
Sign up to set email alerts
|

NDC pledges of South Asia: are the stakeholders onboard?

Abstract: There is no doubt that the adverse impacts of climate change will affect a large proportion of the world's population, especially in South Asia which is home to over 25% of the world's population. The vulnerability of the region is even greater because 33% of the world's poor live in this region (Alam and Rabbani 2007; World Bank 2017). However, for a country to fulfil the commitments made by the national government in the 2015 Paris Agreement (UNFCCC 2015), there is a need for coordinated action among all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Even though the production and distribution of plastic bags is banned in Bangladesh and parts of India, this interdiction is poorly implemented and commonly violated in some places (Hossain, 2002; Gupta, 2011). A recent study found that South Asian stakeholders prefer conversion of waste to energy as a way of managing solid waste properly (Haque et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the production and distribution of plastic bags is banned in Bangladesh and parts of India, this interdiction is poorly implemented and commonly violated in some places (Hossain, 2002; Gupta, 2011). A recent study found that South Asian stakeholders prefer conversion of waste to energy as a way of managing solid waste properly (Haque et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing interest in converting waste to energy, a popular idea in South Asia [31]. Another way to reduce the use of plastics bags is to impose a ban and enforce the ban with significant fines.…”
Section: Discussionmentioning
confidence: 99%
“…The lifespan of the landfill site could be prolonged if waste collection and transfer are carried out separately for degradable and non-degradable waste and degradable waste is either composted or converted to energy [58]. There has been increased interest among South Asian policy makers and stakeholders on converting waste to energy [59]. Further study is needed in order investigate the incentives that would motivate waste collection service providers to collect and transfer degradable and non-degradable waste separately.…”
Section: Discussionmentioning
confidence: 99%